Performance Profiling of Female Youth Netball Players. Issue 11 (November 2020) - McKenzie, Chloe R.; Whatman, Chris; Brughelli, Matt
Abstract : Abstract: McKenzie, CR, Whatman, C, and Brughelli, M. Performance profiling of female youth netball players. J Strength Cond Res 34(11): 3275–3283, 2020—The purpose of this study was to investigate the physical performance characteristics of New Zealand secondary school netball players to provide a physical performance profile and determine whether there are differences between playing grade and playing positions for this group. A total of 102 female netball players (mean ± SD : age 13.3 ± 0.50 years, height 166.95 ± 5.72 cm, and body mass 60.94 ± 12.80 kg) participated in this study. Measurements included anthropometry, horizontal and vertical jump performance, balance, core strength, change-of-direction speed, and split sprint times. Magnitude-based inferences were used to determine differences in all measures. Grade 1 players jumped further and higher (effect size [ES] = 0.41–1.37) and ran faster with small to moderate differences. They demonstrated faster change-of-direction speed (ES = −0.73 to −1.31), greater core strength (ES = 0.28–1.17), and a faster time-to-stabilization (ES = −0.69). Grade 2 circle players jumped further (ES = −0.29), compared with noncircle players who jumped higher (ES = 0.35). Noncircle players had faster sprint and change-of-direction speed (ES = −0.33 to −0.55) and measures of balance (ES = −0.47 to 0.55). Grade 1 circle players were found to be faster over 20 m (ES = 0.75). The results of this study showed differences in the physical performance capabilities between youth netball players competing in different grades, as well as differences between playing positions. These findings have provided a physical performance profile of female youth netball players in New Zealand, suggesting that physical performance measures could be used for position-specific training and talent identification and selection.